Gerenciamento de resultados e Guidance: um estudo em empresas brasileiras - Domingos, Sylvia Rejane Magalhães (2022)
The internal and external forces of organizational environment influence the decisions and actions of managers, especially with regard to accounting. In this way, the manager can manage accounting through the discretion and subjectivity present in accounting choices, through certain incentives. Among them, specifically related to the stock market, we highlight earnings guidance. Considering that earnings guidance is seen as a way for the company to manage stock market expectations, the present study investigated whether the achievement of earnings guidance disclosed by Brazilian companies is explained by earnings management practices. The study sample gathered companies listed on B3 S. A. Brasil, Bolsa, Balcão (formerly Bolsa de Valores, Mercadorias e Futuros – BM&FBovespa) in the period from 2010 to 2020. The research collected and compared the guidance disclosed by the companies regarding accounting indicators and of performance with the numbers actually realized creating the variable error of the achieved earnings guidance. The levels of accounting earnings management were analyzed from two perspectives: accruals earnings management and real earnings management, estimated by the Modified Jones (1995), Pae (2005), Paulo (2007) and Roychowdhury (2006) models. The results indicated that there is a predominance of quantitative and monetary earnings guidance, with annual periodicity, with exact estimation precision and focused on the short term. It is noteworthy that there is no uniformity of disclosure when the type of indicator is evidenced. Analyzing the results of the regression, it appears that in the model in which earnings management is estimated by accrual earnings management, the coefficient of the dependent variable error in reaching the disclosed earnings guidance was negative, while in the model estimated by real earnings management the coefficient was positive and that the interactive variables were significant for both models, indicating that to achieve the earnings guidance disclosed when the projection is above the actual, companies use accruals earnings management, however, when the earnings guidance is below the actual companies use real earnings management. The present study contributed to enrich the discussion on guidance and earnings management, obtaining evidence that investors and the inspection and regulatory bodies of the capital market in Brazil should seek alternatives to detect and/or inhibit opportunistic management practices in companies, whether in disclosing earnings guidance that are more compatible with the companies' capacity, or in curbing earnings management practices to achieve the earnings guidance, which necessarily implies increasing the quality of accounting information.